Assessing the Survival and Coping Mechanisms of Street Children in Kisenyi Slum, Kampala Central Division - Martha Garang Akon (Uganda Christian University, 2023)
This dissertation seeks to explore the complex and challenging lives of street children in the Kisenyi slum, located in Kampala Central Division, Uganda. The research objectives are structured to shed light on the reasons behind children's migration to the streets, the myriad challenges they face, and the survival and coping mechanisms they employ to navigate their daily lives in this harsh urban environment. The objectives aim to uncover the underlying reasons that drive children to the streets in Kisenyi slum. This investigation will delve into the sociodemographic and environmental factors, family dynamics, and economic pressures that contribute to this phenomenon, to focuse on the challenges confronted by street children within the Kisenyi slum. It entails a comprehensive examination of the physical, emotional, and social hardships these children endure, including issues related to food security, healthcare access, education, and exposure to violence and lastly to assess the survival and coping mechanisms adopted by street children in Kisenyi to navigate their daily lives. This research will investigate how these resilient individuals leverage their limited resources and social networks to secure basic necessities and protect themselves from the dangers of street life. However, to address these research objectives, this study will employ a mixed-methods approach, combining qualitative interviews and surveys with street children, their families, and relevant stakeholders, as well as quantitative data analysis to derive meaningful insights into the multifaceted lives of street children in Kisenyi slum. Conclusively, the examination of these research questions seeks to contribute to the broader understanding of the circumstances and experiences of street children in urban slums. It aims to inform policy development, advocacy, and intervention strategies that can provide support and improve the lives of these vulnerable children in Kisenyi slum and similar settings worldwide.
This is a dissertation.